The association between taking a death certificate course and practical knowledge about death certificate among Saudi medical students - Walery Zukow; Norah AlHogail; Saud Alaqeel; Khayyal Alderaan; Abdulla Al-hawamdeh; Hani Alhudhaif (Nicolaus Copernicus University in Toruń, 2022)
In Saudi Arabia, family members, general practitioners, morticians, or police officer, who are eligible to request autopsies, refrain from doing so to expedite the burial of the deceased. Inaccurate entries into the medical death certificate facilitate so. The reason for ignoring the completion of death certificates is not fully explored. Yet, incompetence or avoiding medicolegal allegations seem to be causative factors.  In this study, we conducted a cross-sectional study on 335 medical students from all years of medical school to determine the association between taking the death certificate course and the level of knowledge about death certificates among medical students. The results showed an increase in the level of knowledge of students who took the course compared to the students who did not. Among the students who have seen death certificates, the majority have not seen enough number of death certificates. Cultural mores of the medical students are expected to govern their carefulness in filling out the death certificates.